Differences in boat velocity related to technical efficiency in highly-trained rowers - Holt, A. C.; Siegel, R.; Aughey, R. J.; Hopkins, W. G.; Ball, K. (ISBS Proceedings Archive (Michigan), 2020)
Boat velocity is determined by both physical capacity and technical ability. By adjusting for power, we quantified differences in velocity attributable to technical efficiency. Stroke data from 47 2000 m races in male and female single sculls (10 and 8 boats) and coxless pairs (3 and 6 boats) were collected using Peach PowerLine and OptimEye S5 GPS equipment attached to boats. The logarithm of velocity was predicted with the logarithm of the sum of mean stroke power of both oars in a general linear mixed model for each boat class, a random effect for boat identity estimated a coefficient of variation representing differences in efficiency between boats. The differences were very large to extremely large (CV of 1.3-3.4%). Performance of boats with poor efficiency could be enhanced by improving technique, improving power output could be the focus for those with good efficiency.